2021
DOI: 10.48550/arxiv.2109.05449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nonreciprocal frequency conversion with chiral $Λ$-type atoms

Lei Du,
Yao-Tong Chen,
Yong Li

Abstract: In this paper, we begin with a model of a Λ-type atom whose both transitions are chirally coupled to a waveguide and then extend the model to its giant-atom version. We investigate the singlephoton scatterings of the giant-atom model in both the Markovian and non-Markovian regimes. It is shown that the chiral atom-waveguide couplings enable nonreciprocal, reflectionless, and efficient frequency conversion, while the giant-atom structure introduces intriguing interference effects to the scattering behaviors, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Recently, the atom-waveguide system has been generalized to studies of interactions between the photon in the waveguide and a giant atom, where an artificial atom (quantum emitter) is fabricated to couple multiple points on the waveguide. Due to the fact that multi-path quantum interferences are included in interactions between waveguide photons and giant atoms, a variety of interesting quantum optical phenomena have been explored, including bound states or dressed states [23,[30][31][32][33], decoherence-free interaction [34][35][36][37], electromagnetically-induced transparency [38][39][40][41], and many others [42][43][44][45][46][47][48][49][50][51]. Relevant experiments have also been demonstrated that microwave photons or propagating phonons have been successfully coupled to an artificial gaint atom [35,39,52].…”
mentioning
confidence: 99%
“…Recently, the atom-waveguide system has been generalized to studies of interactions between the photon in the waveguide and a giant atom, where an artificial atom (quantum emitter) is fabricated to couple multiple points on the waveguide. Due to the fact that multi-path quantum interferences are included in interactions between waveguide photons and giant atoms, a variety of interesting quantum optical phenomena have been explored, including bound states or dressed states [23,[30][31][32][33], decoherence-free interaction [34][35][36][37], electromagnetically-induced transparency [38][39][40][41], and many others [42][43][44][45][46][47][48][49][50][51]. Relevant experiments have also been demonstrated that microwave photons or propagating phonons have been successfully coupled to an artificial gaint atom [35,39,52].…”
mentioning
confidence: 99%